2016
DOI: 10.1371/journal.pone.0164412
|View full text |Cite
|
Sign up to set email alerts
|

Handedness, Earnings, Ability and Personality. Evidence from the Lab

Abstract: Evidence showing that on average left-handed (L), who are 10% in a population, tend to earn less than others is solely based on survey data. This paper is the first to test the relationship between handedness and earnings experimentally and also to assess whether the mechanism underlying it is predominantly cognitive or psychological. Data on 432 undergraduate students show that L do not obtain significantly different payoffs, a proxy for earnings, in a stylised labour market with multiple principals and agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…the birth year of the youngest participants, with ~ 0.7 percentage-points per decade ( Figure S2). We attribute this to a decline in enforcing righthandedness, as has been discussed before (Cerhan et al, 1994;Harris, 1993;Salive et al, 1993), rather than reduced survival of non-right-handers (Coren and Halpern, 1991). However, as noted above, it is also possible that unknown environmental influences are involved in handedness, especially prenatally, which might have changed over the decades.…”
Section: Environmental Effectsmentioning
confidence: 73%
See 1 more Smart Citation
“…the birth year of the youngest participants, with ~ 0.7 percentage-points per decade ( Figure S2). We attribute this to a decline in enforcing righthandedness, as has been discussed before (Cerhan et al, 1994;Harris, 1993;Salive et al, 1993), rather than reduced survival of non-right-handers (Coren and Halpern, 1991). However, as noted above, it is also possible that unknown environmental influences are involved in handedness, especially prenatally, which might have changed over the decades.…”
Section: Environmental Effectsmentioning
confidence: 73%
“…As a consequence, a proportion of otherwise left-handed or ambidextrous people has become right-handed, while possibly also a number of left-handed people have become ambidextrous through this enforcing (Vuoksimaa et al, 2009). The rate of enforced right-handedness varies between cultures (Raymond and Pontier, 2004), but has typically shown a decline over recent decades: in many countries, proportions of left-handers have increased with time, probably because society has become more tolerant of variation (Cerhan et al, 1994;Gilbert and Wysocki, 1992;Salive et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…As a striking human behavioural polymorphism, handedness has attracted a lot of attention in both the scientific and popular literature. For example, personality traits and cognitive skills have been claimed to associate with handedness 4,5 . The prevalence of non-right-handedness has also been found to be increased in people with various cognitive or psychiatric disorders 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Left-handers are significantly more agreeable [53] and more emotionally unstable [54], more dominant and less nurturance [55]. As to extraversion, early study [56] demonstrated that righthanders are more extraverted compared to left-handers (only women, not men), however, the results of modern research studies are directly opposite [53]. Another modern study [57] does not reveal any difference between left-and right-handers but demonstrates that the left-handers are more extraverted than the right-handers according to self-estimation of the level of extraversion.…”
Section: Introductionmentioning
confidence: 90%
“…There is evidence that personality traits differ in right-and left-handers. Left-handers are significantly more agreeable [53] and more emotionally unstable [54], more dominant and less nurturance [55]. As to extraversion, early study [56] demonstrated that righthanders are more extraverted compared to left-handers (only women, not men), however, the results of modern research studies are directly opposite [53].…”
Section: Introductionmentioning
confidence: 99%